PEMASARAN ROTI JALA UNTUK MENINGKATKAN EKONOMI KELUARGA DI LINGKUNGAN 18 RENGAS PULAU MEDAN - Sri Wahyuni Tarigan; Widya Fernanda Putri; Anita Christine Sembiring; Uni Pratama Tarigan; Yennimar Yennimar (Smart Education, 2023)
Abstract: Roti jala is a typical food of the Malay people in North Sumatra. This dish is also often found in Riau. In Medan (Deli) North Sumatra, this food is often served with chicken curry or goat curry mixed with pickled pineapple and can also be served with pickled cucumber and carrots. Roti jala is a combination of Indian and Malay cuisine. Along with the development of the times, roti jala is not only sold by the Malay community, now various tribes have made and marketed it, including the community of Environment 18, Rengas Pulau Subdistrict. People in the 18 district of Rengas Pulau generally sell roti jala as an additional income of 70% and a main income of 30% to improve the family economy.Keyword: delicious bread meshAbstrak: Roti jala adalah makanan khas masyarakat Melayu di Sumatera Utara. Hidangan ini juga banyak di temui di Riau. Di Medan (Deli) Sumatera Utara makanan ini sering disajikan dengan gulai kari ayam atau gulai kari kambing di campur acar nenas dan bisa juga dengan acar timun dan wortel. Roti jala merupakan perpaduan masakan India dengan Melayu. Seiring dengan perkembangan zaman roti jala tidak hanya di jual oleh masyrakat Melayu saja, saat ini berbagai suku telah membuat dan memasarkannya termasuk masyrakat Lingkungan 18 Kelurahan Rengas Pulau. Masyarakat di lingkungan 18 Kelurahan Rengas Pulau umumnya menjual roti jala sebagai penghasilan tambahan sebanyak 70% dan penghasilan utama sebanyak 30% untuk meningkatkan ekonomi keluarga.Kata kunci: jala roti